Challenges and opportunities for social sustainability in education: a scoping review - Åsa Nilsson Dahlström (Cogent Social Sciences)
Social sustainability in education is crucial in fulfilling Agenda 2030, yet an area not well represented in research. This scoping review aims at investigating this gap, covering the years 2018 to 2023, with a focus on how social sustainability is defined and implemented in education and what challenges and opportunities for achieving social sustainability that have been identified in the education research in Web of Science, ERIC, and Scopus databases. A total of 120 articles were identified and screened, 76 as full text, and out of these 42 were included in the final analysis. While all articles highlight the vital role of teaching social sustainability in education, some also point out that its broader implementation is hindered by a lack of theoretical and conceptual clarity. This vagueness also creates difficulties in identifying and assessing the impact of social sustainability issues in education. This review focuses on how social sustainability has been defined and implemented in education, what challenges and opportunities for social sustainability issues in education that can be identified, and furthermore how education can contribute to overall sustainability within the frameworks of Education for Sustainable Development (ESD) and Education for Sustainable Development Goals (ESDG).